2019
DOI: 10.1016/j.solmat.2018.11.023
|View full text |Cite
|
Sign up to set email alerts
|

CrAlSiN barrier layer to improve the thermal stability of W/CrAlSiNx/CrAlSiOyNx/SiAlOx solar thermal absorber

Abstract: A B S T R A C TThe influence of adding CrAlSiN barrier layer between the back-reflector tungsten (W) and stainless-steel substrate on thermal stability has been investigated. In previous work, after the annealing in vacuum at 600°C, tungsten diffusion from the back-reflection layer towards the stainless-steel substrate was found. In this study, a barrier layer was added and its influence upon the W diffusion was studied. Several designs of multilayer solar selective absorber for high temperature applications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
1
4
1
Order By: Relevance
“…The SSACs on Cu substrate showed a poor α of 0.88 and ε of 0.062. Such result was different from the traditional four‐layer double‐cermet SSACs, such as W‐Al 2 O 3 , Mo‐SiO 2 , Al‐AlN, and CrAlSiN . Compared with the recently reported multilayer absorbers (Table ), the WO x /SiO 2 SSACs showed similar optical performance, whereas the SSACs presented a simple structure and low process cost.…”
Section: Resultscontrasting
confidence: 62%
“…The SSACs on Cu substrate showed a poor α of 0.88 and ε of 0.062. Such result was different from the traditional four‐layer double‐cermet SSACs, such as W‐Al 2 O 3 , Mo‐SiO 2 , Al‐AlN, and CrAlSiN . Compared with the recently reported multilayer absorbers (Table ), the WO x /SiO 2 SSACs showed similar optical performance, whereas the SSACs presented a simple structure and low process cost.…”
Section: Resultscontrasting
confidence: 62%
“…In all cases, the emittance (ε) is improved after annealing in air and in vacuum, which confirms that the tungsten reflection layer is well protected by the other layers, showing good thermal stability against oxidation. The decrease of the emissivity with annealing was already reported and can be due to a W phase transformation during annealing [22,23]. Fig.…”
Section: Thermal Stabilitysupporting
confidence: 62%
“…As a result, small amount of tungsten diffused towards the stainless-steel substrate, but the general evaluation shows that no other significant changes are present. However, tungsten diffusion towards the substrate can be easily solved by adding a barrier layer, as studied in the previous work [22].…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Thin films have been widely used in different application fields such as in chemical as diffusion barrier, in electrochemical as films for protection against corrosion, in mechanical as hard and wear resistance coating, in optical as reflection and antireflection coating, and in electronic area as conductor or insulator material [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Among all these compounds, we find that the transition metal nitrides (MeN) have been widely used in mechanical applications due to their high hardness and wear resistance [2,[13][14][15][16]. However, it has been found that the addition of a third element may improve the physical and chemical properties of MeN due to a change that this new element generates in the microstructure of these materials [1,[17][18][19][20][21][22][23][24][25][26][27][28][29][30]. These structures are called nanocomposite, and there are two different groups of hard nanocomposite films, for instance: (i) crystalline/amorphous nanocomposites and (ii) crystalline/crystalline nanocomposites.…”
Section: Introductionmentioning
confidence: 99%